CHANGES OF PHYSICAL PROPERTIES OF THE MESH GILL NET BASED ON AGE OF USE IN TIKU V JORONG TANJUNG MUTIARA DISTRICT AGAM REGENCY WEST SUMATERA - Desmayuni, Helfia; Nofrizal, Nofrizal; Isnaniah, Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe fishing gear used by Tiku V Jorong fisherman is gill nets, the use of gill nets by fisherman even reaches the age of use for more than 15 years. Because of this, research was to knowing the changes that occurred after using gill nets after several years. The research was conducted in April 2018 which was held in Nagari Tiku V Jorong, Tanjung Mutiara Subdistrict, Agam Regency, west sumatera. The goal of the research to determine the technical age of using gill nets and to see changes in the physical properties of net gills such as changes in mesh size, elongation and decreasing breaking load after several years of use. The method used in this study is a survey method that is data collection and materials in the research location and method of measurement experiments in the laboratory of the Department of Fisheries Resource Utilization, Riau University. The results of this study indicate that the age of using a net results in a decrease in diameter of yarn mesh, breaking load and elongation with the equation YD (Yarn diameter) = -0.0005t + 0.1840, BL (Breaking Load) = -0.0008t + 0.1889 and ME (Mesh Elongation) = -0.0316t + 10.6161 while the mesh size has increased with the length of life with the equation MZ (Mesh Zise) = 0.0252t + 44.4602 and from the data that has been analyzed the technical age of the gill net is 10 years. Keywords : gill net, mesh size, physical properties, technical age, usage age